Religious Education in School Affects Students' Lives in the Long Run - Benjamin W. Arold; Ludger Woessmann; Larissa Zierow (CESifo Forum, 2022)
Being exposed to compulsory religious education in school can have long-run consequences for students' lives. At different points in time since the 1970s, German states terminated compulsory religious education in public schools and replaced it by a choice between ethics classes and religious education. This article shows that the reform not only led to reduced religiosity in students' later life, but also eroded traditional attitudes towards gender roles and increased labor-market participation and earnings.
Keywords: 330